Substance over Form in Tax Compliance and Risk of Fraud in SelfAssessment System - Danny Wibowo (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Objectives: This study explores the relationship between the accounting principle of substance over form and the self-assessment system in taxation, focusing on its implications for tax policy, fairness, and compliance. Method: Using a Systematic Literature Review (SLR) approach, it examines literature published in English from 1999 to 2024, sourced from databases such as ProQuest, Emerald Insight, Science Direct, Sage Journals, Taylor & Francis Online, and Wiley Online Library, with specific keywords including “Substance,” “Self-assessment,” and “Tax Compliance.” The review applies criteria requiring open access, qualitative methods, and complete content from abstract to conclusion, covering journals, books, and other relevant references. Results: The findings highlight the significance of prioritizing the economic substance of transactions over their legal or formal appearance in determining tax obligations, while also raising critical concerns about taxpayer discretion in reporting based on transaction substance and its potential effects on compliance. Conclusion: Ultimately, the study emphasizes the importance of establishing a clear regulatory framework and strong government oversight to ensure tax justice and prevent unethical tax avoidance practices.